Visual guidance of the human foot during a step - Reynolds, Raymond F.; Day, Brian L. (The Journal of physiology, 2005)
When the intended foot placement changes during a step, either due to an obstacle appearing in our path or the sudden shift of a target, visual input can rapidly alter foot trajectory. However, previous studies suggest that when intended foot placement does not change, the path of the foot is fixed after it leaves the floor and vision has no further influence. Here we ask whether visual feedback can be used to improve the accuracy of foot placement during a normal, unperturbed step. To investigate this we measured foot trajectory when subjects made accurate steps, at fast and slow speeds, to stationary floor-mounted targets. Vision was randomly occluded in 50% of trials at the point of foot-off. This caused an increase in foot placement error, reflecting lower accuracy and higher variability. This effect was greatest for slow steps. Trajectory heading analysis revealed that visually guided corrections occurred as the foot neared the target (on average 64 mm away). They occurred closer to the target for the faster movements thus allowing less time and space to execute corrections. However, allowing for a fixed reaction time of 120 ms, movement errors were detected when the foot was approximately halfway to the target. These results suggest that visual information can be used to adjust foot trajectory during the swing phase of a step when stepping onto a stationary target, even for fast movements. Such fine control would be advantageous when environmental constraints place limitations on foot placement, for example when hiking over rough terrain.